2009
DOI: 10.1136/jmh.2009.001511
|View full text |Cite
|
Sign up to set email alerts
|

Existential boredom: the experience of living on haemodialysis therapy

Abstract: Empathy is an essential component of professional nursing practice. In order to empathise appropriately with patients, it is crucial that nurses appreciate, understand and respond to their patients' experience of illness. This study sought to explore the experiences of 16 people with end stage renal disease on haemodialysis therapy in Ireland. A hermeneutical phenomenological methodology was employed incorporating qualitative interviews. The data were analysed using qualitative interpretive analysis. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…In line with the literature (Al-Arabi, 2006;Bayhakki and Hatthakit, 2012;Calvey and Mee, 2011;Clarkson and Robinson, 2010;Hagren et al, 2001Hagren et al, , 2005Moran et al, 2009;Polaschek, 2003), the most significant issues for participants in this study concerned the physical and psychosocial limitations of being-in-dialysis, elaborated below in terms of restrictions on time, space and lifestyle.…”
Section: Study Data and Discussion: Time Mobility And Spacementioning
confidence: 76%
“…In line with the literature (Al-Arabi, 2006;Bayhakki and Hatthakit, 2012;Calvey and Mee, 2011;Clarkson and Robinson, 2010;Hagren et al, 2001Hagren et al, , 2005Moran et al, 2009;Polaschek, 2003), the most significant issues for participants in this study concerned the physical and psychosocial limitations of being-in-dialysis, elaborated below in terms of restrictions on time, space and lifestyle.…”
Section: Study Data and Discussion: Time Mobility And Spacementioning
confidence: 76%
“…Just as James, Jenny and Wendy describe, patients waiting for a liver transplant (Moran et al, 2009) found that a lack of contact from the team 14 left them feeling forgotten. Some of these liver patients also questioned whether they truly wished to be on the list (Moran et al, 2009), mirroring James's experience and demonstrating the depths of uncertainty some list members feel.…”
Section: Adjusting To the Uncertainty Of Waitingmentioning
confidence: 99%
“…Calvey and Mee (2011) report that haemodialysis highlights a need for patients to define a new sense of self because of the illness. This is due in part to the chronic nature of the illness and the frustration (Polaschek, 2003a), loss of freedom (Hagren, Pettersen, Severinsson, Lützen, & Clyne, 2005), boredom (Moran, Scott, & Darbyshire, 2009) and dependence (Strandberg, Åström, & Norberg, 2002) that the illness creates. Polaschek (2003b) suggests that the strength of qualitative studies is that they offer a better understanding of the experience of people living on haemodialysis, and provide an opportunity for health professionals to gain insight into the experiences of the patient and therefore be able to provide more adequate support and understanding of the issues that haemodialysis patients face.…”
mentioning
confidence: 98%